Brokerage as an urban and regional process between systems and scales. Issue 2 (1st February 2023) - Sigler, Thomas; Neal, Zachary; Martinus, Kirsten
ABSTRACT: Brokerage is a process through which actors gain strategic advantage from being in-between two others. Traditionally, research has focused on people and organizations to understand how brokerage either facilitates or impedes the transmission of information or knowledge, and how this impacts both the actors and their networks. Here, we demonstrate how firms and other economic actors facilitate brokerage between cities and regions by drawing upon research from eight special issue papers. We argue that brokerage is a process connecting cities and regions between scales and between systems . Suggestions for further research focus on process and agency.